2020
DOI: 10.1177/0193945920938048
|View full text |Cite
|
Sign up to set email alerts
|

Brief Workplace Interventions Addressing Burnout, Compassion Fatigue, and Teamwork: A Pilot Study

Abstract: Burnout and compassion fatigue are problematic for nurses, patients, and organizations. Identifying brief interventions nurses can engage in while at work to address compassion fatigue, burnout, and teamwork, as burnout and teamwork are inversely related, is important for all stakeholders. This quasi-experimental pilot study sought to examine the feasibility, acceptability, and effectiveness of five-minute interventions on nurses’ burnout, compassion fatigue, and perceptions of teamwork. Nurses were randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 25 publications
0
30
0
1
Order By: Relevance
“…Previously published evidence suggests that brief, 5-minute interventions offered at the workplace may be effective in reducing burnout and secondary traumatic stress in HCWs. 24,25 However, more frequent participation in the VR experience and/or a longer duration of exposure to the intervention may be needed to significantly affect outcomes. The number of available VR headsets is a barrier to implementing additional sessions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously published evidence suggests that brief, 5-minute interventions offered at the workplace may be effective in reducing burnout and secondary traumatic stress in HCWs. 24,25 However, more frequent participation in the VR experience and/or a longer duration of exposure to the intervention may be needed to significantly affect outcomes. The number of available VR headsets is a barrier to implementing additional sessions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the immersive VR experience was limited to 5 minutes to allow for an impact on the autonomic nervous system even after use of the technology during a quick break. Previously published evidence suggests that brief, 5-minute interventions offered at the workplace may be effective in reducing burnout and secondary traumatic stress in HCWs 24,25 . However, more frequent participation in the VR experience and/or a longer duration of exposure to the intervention may be needed to significantly affect outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Recommended trauma-informed leadership approaches include the following: Encourage staff participation self-care activities while at work (e.g., journaling, walking, mindfulness, meditation, and gratitude activities) Invite a staff member to go on a walk at work and listen to his/her stories If staff members volunteer information about their own past trauma and its subsequent effects, consider their story in interactions with them, particularly in those showing signs of compassion fatigue and burnout Have crucial conversations with staff members who are exhibiting signs of compassion fatigue and burnout, offering a change of job duties or work assignment if possible Diversify or decrease staff workload, particularly in dealing with patients experiencing traumatic events or those admitted with COVID-19 Support staff in having time off work, particularly on evenings, nights, and weekends, and have minimal work-related contact with staff on their days off Allow staff to take vacations and use paid time off when possible Encourage participation in debriefings after difficult or traumatic patient care experiences Educate and encourage staff to have professional boundaries with patients and their families Provide positive recognition of staff in ways that are personally meaningful to the individual staff members Acknowledge and reward staff members who are loyal to the organization (e.g., retention bonuses, extra shift bonuses) Encourage peer support, teamwork, and collaboration Empower and encourage staff in pursuing education, training, and professional development Support employee autonomy, shared decisionmaking, and sense of control in the workplace. 15,16,30,31 Work-Related Injuries Compassion fatigue and burnout, if left untreated, may lead to long-term emotional trauma, depression, and suicide in health care providers. 32 Therefore, compassion fatigue, burnout, and secondary traumatic stress should be treated as on-the-job injuries or workrelated injuries.…”
Section: How Do We Translate Trauma-informed Care Into Leadership?mentioning
confidence: 99%
“…32 Therefore, compassion fatigue, burnout, and secondary traumatic stress should be treated as on-the-job injuries or workrelated injuries. 16,30 Nurse leaders should first attempt to mitigate the effects of compassion fatigue and burnout in employees by using approaches and strategies such as those listed earlier in the study. 30 If unable to mitigate, workplace mental health resources such as employee assistance programs should be instituted as soon as possible.…”
Section: How Do We Translate Trauma-informed Care Into Leadership?mentioning
confidence: 99%
“…It remains to be empirically tested with police, but a recent study demonstrated the value of "interprofessional collaboration and transformative leadership" on reducing symptoms of secondary traumatic stress ( [53], p. 7). Additionally, burnout and compassion fatigue have been shown to be inversely related to teamwork [54,55].…”
Section: Minimizing Emotional and Spiritual Distressmentioning
confidence: 99%